AN AUDIT OF THE INITIATION, PRESCRIPTION AND ADMINISTRATION OF OPIOID ANALGESIA TO ADULT PALLIATIVE CANCER PATIENTS IN AN ACUTE HOSPITAL. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Messam, Kerry; Cooper, Jan
Abstract : Background: Despite a plethora of literature and multiple guidelines, uncontrolled cancer pain remains hugely burdensome to patients. To address inconsistencies and misunderstanding surrounding the use of opioid analgesia in clinical practice, the UK National Institute for Clinical Excellence (NICE 2012) recently introduced national guidance in the form of the opioid care pathway to assist Health Care Professionals with the initiation and titration of opioid analgesia for patients with palliative disease. Aim: This audit measured current practice in the initiation, prescription and administration of opioids in adult cancer patients with palliative disease in an acute hospital setting. Data was collected retrospectively from patient records and prescription/administration charts, to ascertain whether standards on opioid treatment set by NICE (2012), the UK National Patient Safety Agency (2010), UK Nursing and Midwifery Council (2010), and local hospital standards were being achieved. Results: 86 sets of clinical records were retrieved between December 2011 and November 2012. Results demonstrated significant concerns regarding the administration of opioids and a high incidence in PRN prescribing alone, with only 45 patients commenced on regular opioid prescriptions. Of the fifteen audited standards, only a third demonstrated compliance +/-10%. Conclusions: Despite intensive education, opioid initiation, prescription and administration in this group of palliative care patients was not consistent with published guidance and standards. Variations in clinical practice means that audit tools such as NICE (2012) should strongly encourage the recording of explicit exceptions to ensure accurate measurement of practice. Dissemination and collation of feedback is required to inform proposed recommendations, draft prescribing and administration guidance and a re-audit plan.